CiRS-7 Promotes the Proliferation and Migration of Papillary Thyroid Cancer by Negatively Regulating the miR-7/Epidermal Growth Factor Receptor Axis. (22nd June 2020) - Han, Jun-ya; Guo, Si; Wei, Na; Xue, Rui; Li, Wencai; Dong, Gang; Li, Jianhua; Tian, Xiangyu; Chen, Chao; Qiu, Sen; Wang, Tong; Xiao, Qiankun; et al.
Abstract : Purpose . The incidence of papillary thyroid cancer (PTC) is increasing, and traditional diagnostic methods are unsatisfactory. Therefore, identifying novel prognostic markers is very important. ciRS-7 has been found to play an important role in many cancers, but its role in PTC has not been reported. This study was performed to evaluate the biological role and mechanism of ciRS-7 in PTC. Material and Methods . The expression of ciRS-7 in PTC tissues and the matched adjacent tissues was determined by quantitative reverse transcription polymerase chain reaction (qRT-PCR). The PTC cell lines (TPC-1 and BCPAP) were used to evaluate the role of ciRS-7. ciRS-7-siRNA and overexpression plasmid were constructed and transfected into PTC cells. A CCK-8 assay and colony formation assay were performed to explore the effects of ciRS-7 on cell proliferation. Annexin V/PI staining and FACS detection were used to detect cell apoptosis. Wound healing assay was performed to detect cell migration. A transwell assay was conducted to explore the effects of ciRS-7 on invasion and migration. Western blotting was performed to evaluate protein expression. The luciferase reporter system was used to determine the underlying mechanism of miR-7. Result . ciRS-7 was highly expressed in PTC tissues and cell lines compared with the corresponding controls. In vitro study showed that ciRS-7 silencing suppressed proliferation, migration, and invasion of TPC-1 and BCPAP. Mechanistically, the effects of ciRS-7 on invasion and migration may be related to epithelial-mesenchymal transition (EMT). ciRS-7 silencing could attenuate effects on PTC cells induced by miR-7 knockdown. Epidermal growth factor receptor (EGFR), which was demonstrated to be a target of miR-7, decreased significantly in ciRS-7-siRNA PTC cells. Overexpression of EGFR also attenuated effects of PTC cells induced by silencing ciRS-7. Conclusion . ciRS-7 was significantly upregulated in PTC tissues, and it promoted the progression of PTC by regulating the miR-7/EGFR axis. ciRS-7 is a promising prognostic biomarker and therapeutic target in PTC.